Brittle crack propagation acceleration in a single crystal of a 3% silicon-Fe alloy - Tomoya Kawabata; Noritaka Nakamura; Shuji Aihara (Fracture and Structural Integrity)
Brittle fracture in carbon steel has a serious impact on the safety of steel structures. Thus, technology that arrests crack propagation is the final line of protection for such structures. It is such an important issue that conditions that can reliably stop crack propagation should be thoroughly clarified. Due to the social importance of the problem, many experimental and theoretical studies have been conducted from both the mechanical and microstructural viewpoints. Though it has been reported that the upper limit of the speed of brittle crack propagation is theoretically the Rayleigh wave speed, which is approximately 2,900 m/s in steels, the actual speed of brittle crack propagation in steels is approximately 1,000 m/s and lower. The reason for this difference is due to braking effects during crack propagation, for example, unevenness in the faceting, tear ridges, microcracking, twin deformation and side ligaments, which are the elements that dominate the arresting toughness. To evaluate the most fundamental element of the arresting toughness, the authors have studied the crack propagation resistance inside a single crystal and across a grain boundary by using a 3% silicon steel with a microstructure of single phase ferrite and a very large grain size of 4-5 mm. The crack propagation rate inside a single crystal is relatively large, but only half of the Rayleigh wave speed even under the highest stress intensity factor conditions. In this study, the change in the crack propagation rate was measured using small sized multiple-strain gauges that were pasted inside a single crystal along the crack line. From these measurements, crack propagation resistance and the role of grain boundaries are quantitatively discussed in this article